2021
DOI: 10.3389/fneur.2021.760889
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ganglioside Antibodies in Guillain-Barre Syndrome: A Novel Immunoblotting-Panel Assay

Abstract: Objective: This study aimed to determine the diagnostic efficiency of a novel immunoblotting detection assay for anti-ganglioside antibodies (AGAs) in the Guillain–Barre syndrome (GBS).Method: Serum immunoglobulin (IgG and IgM) of AGAs were measured in 121 participants from a registered cohort study of immune-mediated neuropathies and 29 healthy controls by immunoblotting panel assay. Sensitivity, specificity, and positive predictive value (PPV) of the assay were compared to calculate the diagnostic accuracy.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Moreover, we report the first case of the pharyngeal–cervical–brachial variant of GBS associated with COVID-19. In the AMAN variant of GBS, anti-ganglioside antibodies are found to be positive in 86% of cases [20] . While serum anti-ganglioside GM1 antibody was positive in one of our patients, there were no anti-ganglioside antibodies in our other patient.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we report the first case of the pharyngeal–cervical–brachial variant of GBS associated with COVID-19. In the AMAN variant of GBS, anti-ganglioside antibodies are found to be positive in 86% of cases [20] . While serum anti-ganglioside GM1 antibody was positive in one of our patients, there were no anti-ganglioside antibodies in our other patient.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for anti-ganglioside antibodies is important because they are related to the pathomechanism of GBS. A recent cohort study from China analyzed the relationship between immunemediated peripheral neuropathy and serum levels of anti-ganglioside IgG and IgM antibodies 23 . In this cohort, 42.4% patients were positive for at least one of the anti-ganglioside antibodies, and the sensitivity and specificity of the diagnostic test for GBS was 42% and 76%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, GM1 antibody was reported to be common in GBS patients in several other populations, including Korean,[ 22 ] Spanish,[ 13 ] and Chinese. [ 23 ] It is important to note that the presence of GM1 antibody has been associated with the severity and prognosis of GBS. [ 24 25 ] Autoantibody against GM1 from patients with GBS was observed to impede voltage-gated calcium channels (Ca +2 v).…”
Section: Discussionmentioning
confidence: 99%